Enhancing Learning Outcomes in Electronic and Digital Engineering through Interactive Teaching Modules - Mulyadi Nur; Fatmawati Sabur (AL-ISHLAH: Jurnal Pendidikan, 2026)
The development of instructional modules is crucial for enhancing the effectiveness and efficiency of learning. In Electronics and Digital Engineering education, current practices combine student-centered and teacher-centered approaches; however, existing modules remain predominantly printed and lack interactivity, limiting students’ conceptual understanding. This study employed a Research and Development (RD) approach using the Alessi and Trollip model, consisting of planning, design, and development stages. Data were collected through questionnaires, tests, interviews, and observations. Instruments were validated by material and media experts, and reliability testing using Cronbach’s Alpha yielded a coefficient of 0.87, indicating high internal consistency. A purposive sample of 48 students participated, divided into small and large groups for feasibility and effectiveness testing. Quantitative data were obtained during Alpha Test 1 and Alpha Test 2. The implementation of the interactive flipbook-based module resulted in an average post-test score of 83.5%. The normalized gain (N-Gain) between pre-test and post-test scores was 0.7, categorized as high, indicating substantial improvement in students’ conceptual understanding. The findings demonstrate that interactive teaching modules significantly enhance learning outcomes compared to traditional printed materials. The integration of interactivity supports both instructional approaches and facilitates deeper conceptual comprehension. Thus, the developed flipbook module is an effective supplementary learning medium in Electronics and Digital Engineering education.